LAMINATE AND DISPLAY DEVICE
A laminate structure with a glass base, bonding, and deformation suppressing layer addresses the vulnerability of thin glass in flexible displays by enhancing both bending and impact resistance, ensuring safety and durability.
Patent Information
- Application Number
- JP2020183235
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-10-30
AI Technical Summary
Thin glass substrates used in flexible displays, such as foldable displays, become more susceptible to breakage and impact damage due to their reduced thickness, compromising both bending resistance and impact resistance, which can lead to safety hazards.
A laminate structure comprising a glass base material, a bonding layer, and a deformation suppressing layer with a predetermined composite modulus is introduced, where the bonding layer is thinner than the glass base material, enhancing both bending and impact resistance.
The laminate provides improved bending resistance and impact resistance, reducing the risk of breakage and injury from glass fragments, making it suitable for flexible displays and other applications requiring durability.
Smart Images

Figure 0007615613000011 
Figure 0007615613000012 
Figure 0007615613000013
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate having a glass substrate and a display device using the same. [Background technology]
[0002] Thin plate glass has excellent hardness and heat resistance, but has problems in that it is difficult to bend and breaks easily when dropped. For this reason, in recent years, development of ultra-thin glass (UTG), which is made thinner so that it can be bent, has been progressing. Among glass, chemically strengthened glass has a particularly high bending resistance, and by incorporating an expansion stress into the glass surface, it prevents minute scratches on the glass surface from becoming larger when the glass is bent, making the glass less likely to break.
[0003] For example, in the display field, there is a demand for flexibility. In recent years, flexible displays such as foldable displays, rollable displays, and bendable displays have been actively developed, and among them, development of foldable displays, that is, displays that can be bent, is progressing. The use of ultra-thin glass for such flexible displays is being considered.
[0004] For example, Patent Document 1 proposes a glass article comprising a first glass layer, a second glass layer disposed adjacent to the first glass layer, and an interface slidably bonding the first glass layer to the second glass layer, the interface having a thickness of 2 nm to 500 nm, the first glass layer and the second glass layer being 10 μm to 125 μm thick, (a) the article is not broken when held at 25° C. and a parallel plate separation distance of 10 mm for 60 minutes at 25° C. and 50% relative humidity, and (b) the second glass layer is supported by (i) a 50 μm thick adhesive having an elastic modulus of less than 1 GPa and (ii) an approximately 100 μm thick polyethylene terephthalate layer having an elastic modulus of less than 10 GPa, and the first glass layer has a puncture resistance of more than approximately 6 kgf (approximately 58.8 N) when loaded with a tungsten carbide ball having a diameter of 1 mm.
[0005] Furthermore, for example, Patent Document 2 proposes a chemically strengthened ultra-thin glass article having a thickness of 0.4 mm or less, which has a breaking height (in mm) exceeding the value obtained by multiplying the thickness (t) of the glass article (t (mm)) by 50, and further has a breaking bending radius (in mm) less than the value obtained by multiplying the thickness (t (mm)) of the article by 100,000 and dividing the result by the numerical value of the surface compressive stress (MPa) measured on the first surface. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2020-500143 [Patent Document 2] Special Publication No. 2020-521699 Summary of the Invention [Problem to be solved by the invention]
[0007] Although glass can be bent by being made thinner, and its bending resistance improves, the thinner glass also becomes more fragile, and its impact resistance dramatically deteriorates. If glass is broken by an external impact, when it is used as a cover member for a display device, not only will the function of protecting the display device be reduced, but the resulting fragments and sharp edges may injure the fingertips of the user.
[0008] The present disclosure has been made in consideration of the above-mentioned circumstances, and has a main object to provide a laminate having good flex resistance and impact resistance and improved safety. [Means for solving the problem]
[0009] In order to solve the above problems, the inventors of the present disclosure conducted intensive research and found that by disposing a layer having a predetermined composite elastic modulus on the back surface of a thin glass substrate via a bonding layer and setting the thickness of the bonding layer within a predetermined range, it is possible to achieve both good bending resistance and impact resistance. The present disclosure is based on such findings.
[0010] One embodiment of the present disclosure provides a laminate having a glass substrate, a bonding layer, and a deformation suppression layer, in that order, wherein the thickness of the glass substrate is 100 μm or less, the composite elastic modulus of the deformation suppression layer is 7.0 GPa or more, and the thickness of the bonding layer is thinner than the thickness of the glass substrate.
[0011] In the present disclosure, the bonding layer preferably has a composite elastic modulus of 1.0 MPa or more and 1.9 GPa or less.
[0012] In the present disclosure, the deformation suppression layer is preferably a glass layer. The deformation suppression layer may be a resin layer containing a polyimide resin or an aramid resin.
[0013] In addition, the laminate according to the present disclosure preferably has a shatterproof layer on the surface of the glass substrate opposite to the bonding layer.
[0014] The laminate according to the present disclosure may also have a hard coat layer on the side of the shatterproof layer opposite to the glass substrate.
[0015] Moreover, in the laminate according to the present disclosure, it is preferable that the total light transmittance is 80% or more and the haze is 2% or less.
[0016] Another embodiment of the present disclosure provides a display device comprising a display panel and the above-described laminate arranged on an observer side of the display panel, the laminate being arranged so that the surface of the deformation suppression layer faces the display panel.
[0017] The display device in the present disclosure is preferably foldable. Effect of the Invention
[0018] The present disclosure has an effect of providing a laminate having good flex resistance and impact resistance and improved safety. [Brief description of the drawings]
[0019] [Figure 1] 1 is a schematic cross-sectional view illustrating a laminate according to the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view illustrating a laminate according to the present disclosure. [Diagram 3] FIG. 1 is a schematic diagram for explaining a dynamic bending test. [Figure 4] FIG. 1 is a schematic diagram for explaining a static bending test. [Diagram 5] 1 is a schematic cross-sectional view illustrating a display device according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The following describes the embodiments of the present disclosure with reference to the drawings. However, the present disclosure can be implemented in many different forms, and should not be interpreted as being limited to the description of the embodiments exemplified below. In addition, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the actual form in order to make the explanation clearer, but these are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those described above with respect to the previous figures may be given the same reference numerals, and detailed explanations may be omitted as appropriate.
[0021] In this specification, when describing a mode in which another component is disposed on a certain component, the term "above" or "below" is used, unless otherwise specified, to include both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween. Also, in this specification, when describing a mode in which another component is disposed on the surface of a certain component, the term "on the surface side" or "on the surface" is used, unless otherwise specified, to include both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween.
[0022] The laminate and the display device according to the present disclosure will be described in detail below.
[0023] A. Laminate The laminate in the present disclosure comprises, in that order, a glass substrate, a bonding layer, and a deformation suppression layer, the thickness of the glass substrate being 100 μm or less, the composite elastic modulus of the deformation suppression layer being 7.0 GPa or more, and the thickness of the bonding layer being thinner than the thickness of the glass substrate.
[0024] Fig. 1 is a schematic cross-sectional view showing an example of a laminate according to the present disclosure. As shown in Fig. 1, the laminate 1 includes a glass substrate 2 having a predetermined thickness, a bonding layer 3 thinner than the thickness of the glass substrate 2, and a deformation suppression layer 4 having a predetermined composite elastic modulus.
[0025] In the laminate of the present disclosure, the glass substrate is thin, with a thickness of a predetermined value or less, and therefore the bending resistance can be improved. On the other hand, since the glass substrate is thin, with a thickness of a predetermined value or less, there is a concern that it is easily broken and has low impact resistance. In contrast, in the present disclosure, a glass substrate having a predetermined thickness, a bonding layer having a predetermined thickness, and a deformation suppression layer having a predetermined composite elastic modulus are arranged in this order, thereby maintaining good bending resistance while improving impact resistance. The reason for this is presumed to be as follows.
[0026] The inventors of the present disclosure have conducted extensive research into cracking and breakage of a glass substrate due to an impact, and have newly discovered that when an impact is applied instantaneously and locally to the front surface of a glass substrate, the glass substrate is instantaneously and locally deformed, and tensile stress is instantaneously and locally generated on the rear surface of the glass substrate, causing the rear surface of the glass substrate to be unable to withstand the tensile stress and resulting in cracking or breakage.
[0027] In the laminate of the present disclosure, a deformation suppression layer having a predetermined composite elastic modulus is disposed on the rear surface of the glass substrate via a bonding layer having a predetermined thickness, so that instantaneous and local deformation of the glass substrate due to impact from the surface of the glass substrate can be suppressed, and instantaneous and local tensile stress can be suppressed on the rear surface of the glass substrate. In addition, since the bonding layer is usually softer than the glass substrate and the deformation suppression layer having a predetermined composite elastic modulus, it is easily deformed by impact, and the thicker the bonding layer is, the greater the degree of deformation due to impact tends to be. Therefore, by making the thickness of the bonding layer thinner than the thickness of the glass substrate, the degree of deformation of the bonding layer can be reduced when an impact is applied from the surface of the glass substrate, and as a result, instantaneous and local deformation of the glass substrate due to impact from the surface of the glass substrate can be suppressed, and instantaneous and local tensile stress can be suppressed on the rear surface of the glass substrate. Therefore, in the present disclosure, it is possible to improve impact resistance.
[0028] In this way, in the present disclosure, it is possible to achieve both bending resistance and impact resistance. In addition, even if the glass substrate in the laminate is broken, the risk of injury to the human body can be reduced, and the laminate can be made highly safe. Therefore, the laminate in the present disclosure can be folded and used for a wide variety of applications. The laminate in the present disclosure can be used, for example, in a wide variety of display devices, and specifically, can be used as a member for a foldable display.
[0029] Hereinafter, each component of the laminate according to the present disclosure will be described.
[0030] 1. Deformation suppression layer The deformation suppression layer in the present disclosure is a layer disposed on one side of the glass substrate to suppress instantaneous and local deformation of the glass substrate due to impact. When the laminate in the present disclosure is disposed on the observer side of the display panel of a display device, for example, the laminate is disposed so that the surface of the deformation suppression layer faces the display panel. When the laminate in the present disclosure is disposed on the surface of a resin molded product, for example, the laminate is disposed so that the surface of the deformation suppression layer faces the resin molded product.
[0031] (1) Characteristics of the deformation suppression layer In the present disclosure, the composite elastic modulus of the deformation suppression layer is 7.0 GPa or more, preferably 7.3 GPa or more, and more preferably 7.5 GPa or more. By the composite elastic modulus of the deformation suppression layer being within the above range, the instantaneous and local deformation of the glass substrate due to impact can be suppressed, and the cracking of the glass substrate due to impact can be suppressed, thereby improving the impact resistance. On the other hand, the composite elastic modulus of the deformation suppression layer is, for example, 100 GPa or less, may be 90 GPa or less, or may be 80 GPa or less.
[0032] Here, the composite elastic modulus of the deformation suppression layer is defined as the indentation hardness (H IT ) is measured using the contact projection area A pThe indentation hardness is calculated using the formula: "Indentation hardness" is a value determined from a load-displacement curve from loading to unloading of the indenter obtained by hardness measurement using the nanoindentation method. The composite elastic modulus of the deformation suppression layer is an elastic modulus including the elastic deformation of the deformation suppression layer and the elastic deformation of the indenter.
[0033] Indentation hardness (H IT ) is measured on the measurement sample using a "TI950 TriboIndenter" manufactured by BRUKER. Specifically, first, a block is prepared by embedding a laminate cut into 1 mm x 10 mm in embedding resin, and a uniform slice having a thickness of 50 nm to 100 nm without holes is cut out from this block by a general slice preparation method. An "Ultramicrotome EM UC7" (manufactured by Leica Microsystems) or the like can be used to prepare the slice. The remaining block from which the uniform slice without holes is cut out is used as the measurement sample. Next, in the cross section obtained by cutting out the slice in such a measurement sample, a Berkovich indenter (triangular pyramid, TI-0039 manufactured by BRUKER) is pressed vertically into the center of the cross section of the deformation suppression layer for 10 seconds to a maximum pressing load of 25 μN under the following measurement conditions. Here, in order to avoid the influence of the glass substrate and the bonding layer and the influence of the side edges of the deformation suppression layer, the Berkovich indenter is pressed into a portion of the deformation suppression layer that is 500 nm away from the interface between the bonding layer and the deformation suppression layer toward the center of the deformation suppression layer, and 500 nm away from each of both ends of the deformation suppression layer toward the center of the deformation suppression layer. If an arbitrary layer is present on the surface of the deformation suppression layer opposite to the bonding layer side, the indenter is pressed into a portion of the deformation suppression layer that is 500 nm away from the interface between this arbitrary layer and the deformation suppression layer toward the center of the deformation suppression layer. Thereafter, the pressure is held constant to relax the residual stress, and the pressure is then removed over 10 seconds to measure the maximum load after relaxation, and the maximum load P max (μN) and contact projection area A p (nm 2 ) and P max / A p The indentation hardness (HIT The above contact projected area is the contact projected area corrected for the indenter tip curvature by the Oliver-Pharr method using a standard sample of fused quartz (5-0098 manufactured by BRUKER). Indentation hardness (H IT ) is the arithmetic average of values obtained by measuring at 10 points. If any of the measured values deviate from the arithmetic average by more than ±20%, those measured values shall be excluded and remeasured. Whether or not any of the measured values deviate from the arithmetic average by more than ±20% shall be judged by whether the value (%) calculated by (AB) / B x 100, where A is the measured value and B is the arithmetic average, is more than ±20%. Indentation hardness (H IT ) can be adjusted by the type of material contained in the deformation suppression layer, which will be described later.
[0034] (Measurement condition 1) ·Loading speed: 2.5μN / sec ·Holding time: 5 seconds ·Loading and unloading speed: 2.5μN / sec ·Measurement temperature: 25℃
[0035] When the indentation hardness is measured under the above measurement condition 1, if the indentation depth at the maximum load is 500 nm or more, the measurement is to be performed under the following measurement condition 2. As described above, in the measurement of the indentation hardness, the deformation suppression layer is indented for 10 seconds, so that the maximum load under measurement condition 1 is 25 μN and the maximum load under measurement condition 2 is 5 μN.
[0036] (Measurement condition 2) ·Loading speed: 0.5μN / sec ·Holding time: 5 seconds ·Loading and unloading speed: 0.5μN / sec ·Measurement temperature: 25℃
[0037] Composite elastic modulus of deformation suppression layer E r is the contact projection area A obtained during the measurement of indentation hardness according to the following formula (1). pThe composite elastic modulus is calculated by measuring the indentation hardness at 10 points, calculating the composite elastic modulus each time, and taking the arithmetic average of the composite elastic moduli obtained at the 10 points.
[0038]
number
[0039] (In the above formula (1), A p is the contact projected area, and E r is the composite elastic modulus of the deformation suppression layer, and S is the contact stiffness.)
[0040] When the laminate according to the present disclosure is used in, for example, a display device, the deformation suppression layer is preferably transparent. Specifically, the total light transmittance of the deformation suppression layer is preferably 80% or more, more preferably 85% or more, and even more preferably 88% or more.
[0041] The total light transmittance of the deformation suppression layer can be measured in accordance with JIS K7361-1, for example, by a haze meter HM150 manufactured by Murakami Color Research Laboratory. The same method for measuring the total light transmittance of the other layers can be used below.
[0042] The haze of the deformation suppression layer is, for example, preferably 2% or less, more preferably 1.5% or less, and even more preferably 1% or less.
[0043] The haze of the deformation suppression layer can be measured in accordance with JIS K-7136, for example, by a haze meter HM150 manufactured by Murakami Color Research Laboratory. The same method can be used to measure the haze of other layers.
[0044] (2) Thickness of the deformation suppression layer The thickness of the deformation suppression layer is not particularly limited as long as it can suppress instantaneous and local deformation of the glass substrate due to impact, and is preferably 25 μm or more, more preferably 27 μm or more, and even more preferably 29 μm or more. The thicker the deformation suppression layer, the more the impact resistance can be improved. On the other hand, the thickness of the deformation suppression layer is preferably equal to or less than the thickness of the glass substrate, and is preferably, for example, 100 μm or less, more preferably 90 μm or less, and even more preferably 80 μm or less. If the thickness of the deformation suppression layer is too thick, the bending resistance may decrease. If the thickness of the deformation suppression layer is within the above range, the impact resistance can be improved while maintaining the bending resistance.
[0045] Here, the thickness of the deformation suppression layer can be the average value of thicknesses at any 10 locations obtained by measuring a cross section of the laminate in the thickness direction observed by a transmission electron microscope (TEM), a scanning electron microscope (SEM), or a scanning transmission electron microscope (STEM). Unless otherwise specified, the same method can be used to measure the thicknesses of other layers in the laminate.
[0046] (3) Material of deformation suppression layer The deformation suppression layer is not particularly limited as long as it satisfies the above-mentioned composite elastic modulus, and examples thereof include a glass layer and a resin layer containing a polyimide resin or an aramid resin. Among them, the deformation suppression layer is preferably a glass layer. The glass layer usually has a larger composite elastic modulus than the resin layer, and therefore can improve impact resistance.
[0047] (a) Glass layer When the deformation suppression layer is a glass layer, the glass constituting the glass layer can be the same as the glass constituting the glass substrate described below.
[0048] (b) Resin layer When the deformation suppression layer is a resin layer, examples of the resin contained in the resin layer include polyimide resins and aramid resins.
[0049] (i) Polyimide resin In this specification, the polyimide resin refers to a polymer having an imide bond in the main chain. The polyimide resin is not particularly limited as long as it satisfies the above-mentioned composite elastic modulus, and examples thereof include polyimide and polyamideimide.
[0050] (i-1) Polyimide The polyimide is obtained by reacting a tetracarboxylic acid component with a diamine component. The polyimide is not particularly limited as long as it satisfies the above-mentioned composite elastic modulus and has transparency, but it is preferable that the polyimide has at least one structure selected from the group consisting of structures represented by the following general formula (1) and the following general formula (3) in terms of excellent transparency and excellent rigidity.
[0051] [ka]
[0052] In the above general formula (1), R 5 is a tetravalent group which is a tetracarboxylic acid residue, R 6 represents at least one divalent group selected from the group consisting of a trans-cyclohexanediamine residue, a trans-1,4-bismethylenecyclohexanediamine residue, a 4,4'-diaminodiphenylsulfone residue, a 3,4'-diaminodiphenylsulfone residue, and a divalent group represented by the following general formula (2): n represents the number of repeating units and is 1 or more.
[0053] [ka]
[0054] In the above general formula (2), R 7 and R 8 each independently represents a hydrogen atom, an alkyl group, or a perfluoroalkyl group.
[0055] [ka]
[0056] In the above general formula (3), R 9 R represents at least one tetravalent group selected from the group consisting of a cyclohexanetetracarboxylic acid residue, a cyclopentanetetracarboxylic acid residue, a dicyclohexane-3,4,3',4'-tetracarboxylic acid residue, and a 4,4'-(hexafluoroisopropylidene)diphthalic acid residue; 10 represents a divalent group which is a diamine residue, and n' represents the number of repeating units and is 1 or more.
[0057] The term "tetracarboxylic acid residue" refers to a residue obtained by removing four carboxyl groups from a tetracarboxylic acid, and has the same structure as a residue obtained by removing an acid dianhydride structure from a tetracarboxylic dianhydride, and the term "diamine residue" refers to a residue obtained by removing two amino groups from a diamine.
[0058] In the above general formula (1), R 5 is a tetracarboxylic acid residue, and can be a residue obtained by removing an acid dianhydride structure from a tetracarboxylic acid dianhydride. Examples of the tetracarboxylic acid dianhydride include those described in International Publication No. 2018 / 070523. R in the above general formula (1) 5Among them, from the viewpoint of improving transparency and improving rigidity, it is preferable to include at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic acid residue, 3,3',4,4'-biphenyltetracarboxylic acid residue, pyromellitic acid residue, 2,3',3,4'-biphenyltetracarboxylic acid residue, 3,3',4,4'-benzophenonetetracarboxylic acid residue, 3,3',4,4'-diphenylsulfonetetracarboxylic acid residue, 4,4'-oxydiphthalic acid residue, cyclohexanetetracarboxylic acid residue, and cyclopentanetetracarboxylic acid residue, and it is further preferable to include at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic acid residue, 4,4'-oxydiphthalic acid residue, and 3,3',4,4'-diphenylsulfonetetracarboxylic acid residue.
[0059] R 5 In the present invention, the total amount of these suitable residues is preferably 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more.
[0060] Also, R 5 It is also preferable to use a mixture of a tetracarboxylic acid residue group (Group A) suitable for improving rigidity, such as at least one selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic acid residues, 3,3',4,4'-benzophenonetetracarboxylic acid residues, and pyromellitic acid residues, and a tetracarboxylic acid residue group (Group B) suitable for improving transparency, such as at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic acid residues, 2,3',3,4'-biphenyltetracarboxylic acid residues, 3,3',4,4'-diphenylsulfonetetracarboxylic acid residues, 4,4'-oxydiphthalic acid residues, cyclohexanetetracarboxylic acid residues, and cyclopentanetetracarboxylic acid residues.
[0061] In this case, the content ratio of the tetracarboxylic acid residue group suitable for improving the rigidity (Group A) to the tetracarboxylic acid residue group suitable for improving the transparency (Group B) is preferably 0.05 mol or more and 9 mol or less, more preferably 0.1 mol or more and 5 mol or less, and even more preferably 0.3 mol or more and 4 mol or less, of the tetracarboxylic acid residue group suitable for improving the rigidity (Group A) per 1 mol of the tetracarboxylic acid residue group suitable for improving the transparency (Group B).
[0062] R in the above general formula (1) 6 Among them, from the viewpoint of improving transparency and rigidity, it is preferable that the divalent group is at least one selected from the group consisting of 4,4'-diaminodiphenyl sulfone residue, 3,4'-diaminodiphenyl sulfone residue, and divalent groups represented by the above general formula (2), and further, it is preferable that the divalent group is at least one selected from the group consisting of 4,4'-diaminodiphenyl sulfone residue, 3,4'-diaminodiphenyl sulfone residue, and R 7 and R 8 is preferably at least one divalent group selected from the group consisting of divalent groups represented by the above general formula (2), which is a perfluoroalkyl group.
[0063] R in the above general formula (3) 9 Among these, from the viewpoints of improving transparency and rigidity, it is preferable to include a 4,4'-(hexafluoroisopropylidene)diphthalic acid residue, a 3,3',4,4'-diphenylsulfonetetracarboxylic acid residue, and an oxydiphthalic acid residue.
[0064] R 9 In the above, these suitable residues are preferably contained in an amount of 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more.
[0065] R in the above general formula (3) 10is a diamine residue, and can be a residue obtained by removing two amino groups from a diamine. Examples of diamines include those described in International Publication No. 2018 / 070523. R in the above general formula (3) 10 Among these, from the viewpoint of improving transparency and rigidity, 2,2'-bis(trifluoromethyl)benzidine residue, bis[4-(4-aminophenoxy)phenyl]sulfone residue, 4,4'-diaminodiphenyl sulfone residue, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane residue, bis[4-(3-aminophenoxy)phenyl]sulfone residue, 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether residue, 1,4-bis[4-amino-2-(trifluoromethyl)phenoxy]benzene residue, 2,2-bis[4-(4-amino-2-trifluoromethylphenyl] It is preferable that the aryl group contains at least one divalent group selected from the group consisting of a 2,2'-bis(trifluoromethyl)benzidine residue, a bis[4-(4-aminophenoxy)phenyl]hexafluoropropane residue, a 4,4'-diamino-2-(trifluoromethyl)diphenyl ether residue, a 4,4'-diaminobenzanilide residue, an N,N'-bis(4-aminophenyl)terephthalamide residue, and a 9,9-bis(4-aminophenyl)fluorene residue, and it is further preferable that the aryl group contains at least one divalent group selected from the group consisting of a 2,2'-bis(trifluoromethyl)benzidine residue, a bis[4-(4-aminophenoxy)phenyl]sulfone residue, and a 4,4'-diaminodiphenyl sulfone residue.
[0066] R 10 In the present invention, the total amount of these suitable residues is preferably 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more.
[0067] Also, R 10and a diamine residue group (Group C) suitable for improving rigidity, such as at least one selected from the group consisting of bis[4-(4-aminophenoxy)phenyl]sulfone residue, 4,4'-diaminobenzanilide residue, N,N'-bis(4-aminophenyl)terephthalamide residue, paraphenylenediamine residue, metaphenylenediamine residue, and 4,4'-diaminodiphenylmethane residue; and a diamine residue group (Group C) suitable for improving rigidity, such as at least one selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine residue, 4,4'-diaminodiphenylsulfone residue, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane residue, bis[4-(3-aminophenoxy)phenyl]hexafluoropropane residue, It is also preferred to use a mixture of diamine residues suitable for improving transparency (Group D), such as at least one selected from the group consisting of 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether residue, 1,4-bis[4-amino-2-(trifluoromethyl)phenoxy]benzene residue, 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane residue, 4,4'-diamino-2-(trifluoromethyl)diphenyl ether residue, and 9,9-bis(4-aminophenyl)fluorene residue.
[0068] In this case, the content ratio of the diamine residue group suitable for improving the rigidity (Group C) to the diamine residue group suitable for improving the transparency (Group D) is preferably 0.05 mol or more and 9 mol or less of the diamine residue group suitable for improving the rigidity (Group C) per 1 mol of the diamine residue group suitable for improving the transparency (Group D), more preferably 0.1 mol or more and 5 mol or less, and even more preferably 0.3 mol or more and 4 mol or less.
[0069] In the structures represented by the general formula (1) and the general formula (3), n and n' each independently represent the number of repeating units, and are 1 or more. The number of repeating units n in the polyimide may be appropriately selected according to the structure, and is not particularly limited. The average number of repeating units may be, for example, 10 or more and 2000 or less, and preferably 15 or more and 1000 or less.
[0070] The polyimide may partially contain a polyamide structure, for example, a polyamideimide structure containing a tricarboxylic acid residue such as trimellitic anhydride, or a polyamide structure containing a dicarboxylic acid residue such as terephthalic acid.
[0071] In order to improve transparency and surface hardness, R 5 and R 9 and R 6 and R 10At least one of the divalent groups which are diamine residues of the above preferably contains an aromatic ring and at least one selected from the group consisting of (i) a fluorine atom, (ii) an aliphatic ring, and (iii) a structure in which aromatic rings are linked together by an alkylene group which may be substituted with a sulfonyl group or fluorine. When the polyimide contains at least one selected from a tetracarboxylic acid residue having an aromatic ring and a diamine residue having an aromatic ring, the molecular skeleton becomes rigid, the orientation is enhanced, and the surface hardness is improved, but the rigid aromatic ring skeleton tends to have an absorption wavelength which extends to a long wavelength, and the transmittance in the visible light region tends to decrease. On the other hand, when the polyimide contains (i) a fluorine atom, the transparency is improved because the electronic state in the polyimide skeleton can be made difficult to transfer charges. In addition, when the polyimide contains (ii) an aliphatic ring, the transparency is improved because the conjugation of π electrons in the polyimide skeleton can be cut off, thereby inhibiting the transfer of charges in the skeleton. In addition, when the polyimide contains (iii) a structure in which aromatic rings are linked together via a sulfonyl group or an alkylene group which may be substituted with fluorine, the conjugation of π electrons in the polyimide skeleton can be broken, thereby inhibiting the movement of charges in the skeleton, thereby improving transparency.
[0072] Among them, R is the most popular because it improves transparency and surface hardness. 5 and R 9 and R 6 and R 10 At least one of the divalent groups which are diamine residues preferably contains an aromatic ring and a fluorine atom, and R 6 and R 10 It is preferable that the divalent group which is the diamine residue contains an aromatic ring and a fluorine atom.
[0073] Specific examples of such polyimides include those having a specific structure described in WO 2018 / 070523.
[0074] The polyimide can be synthesized by a known method. Alternatively, a commercially available polyimide may be used. An example of a commercially available polyimide product is Neoprim (registered trademark) manufactured by Mitsubishi Gas Chemical Company, Inc.
[0075] The weight-average molecular weight of the polyimide is, for example, preferably from 3,000 to 500,000, more preferably from 5,000 to 300,000, and even more preferably from 10,000 to 200,000. If the weight-average molecular weight is too small, sufficient strength may not be obtained, and if the weight-average molecular weight is too large, the viscosity increases and the solubility decreases, so that a base layer having a smooth surface and uniform thickness may not be obtained.
[0076] The weight-average molecular weight of polyimide can be measured by gel permeation chromatography (GPC). Specifically, polyimide is dissolved in N-methylpyrrolidone (NMP) at a concentration of 0.1% by mass, and a 30 mmol% LiBr-NMP solution with a water content of 500 ppm or less is used as the developing solvent. Measurements are performed using a Tosoh GPC device (HLC-8120, column used: SHODEX GPC LF-804) with a sample injection volume of 50 μL, a solvent flow rate of 0.4 mL / min, and 37°C. The weight-average molecular weight is determined based on a polystyrene standard sample with the same concentration as the sample.
[0077] (i-2) Polyamide-imide The polyamideimide is not particularly limited as long as it satisfies the above-mentioned composite elastic modulus and has transparency, and examples thereof include those having a first block containing a dianhydride-derived structural unit and a diamine-derived structural unit, and a second block containing an aromatic dicarbonyl compound-derived structural unit and an aromatic diamine-derived structural unit. In the above polyamideimide, the dianhydride can include, for example, biphenyltetracarboxylic dianhydride (BPDA) and 2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA). The diamine can include bistrifluoromethylbenzidine (TFDB). That is, the above polyamideimide has a structure obtained by imidizing a polyamideimide precursor having a first block in which a monomer containing a dianhydride and a diamine is copolymerized, and a second block in which a monomer containing an aromatic dicarbonyl compound and an aromatic diamine is copolymerized. The above polyamideimide has excellent optical properties as well as thermal and mechanical properties by having a first block containing an imide bond and a second block containing an amide bond. In particular, the use of bistrifluoromethylbenzidine (TFDB) as the diamine forming the first block can improve the thermal stability and optical properties. In addition, the use of 2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA) and biphenyltetracarboxylic dianhydride (BPDA) as the dianhydride forming the first block can improve the birefringence and ensure the heat resistance.
[0078] The dianhydride forming the first block includes two kinds of dianhydrides, i.e., 6FDA and BPDA. The first block may contain a polymer bound to TFDB and 6FDA and a polymer bound to TFDB and BPDA, which may be separated based on a different repeating unit, or may be regularly arranged in the same repeating unit, or may be completely randomly arranged.
[0079] Of the monomers forming the first block, it is preferable that BPDA and 6FDA are contained as the dianhydride in a molar ratio of 1:3 to 3:1. This is because it is possible to not only ensure the optical properties but also to suppress deterioration of the mechanical properties and heat resistance, and to have excellent birefringence.
[0080] The molar ratio of the first block and the second block is preferably 5:1 to 1:1. When the content of the second block is extremely low, the effect of improving the thermal stability and mechanical properties by the second block may not be sufficiently obtained. When the content of the second block is higher than the content of the first block, the thermal stability and mechanical properties can be improved, but the optical properties may be deteriorated, such as a decrease in yellowness and transmittance, and the birefringence properties may also be increased. The first block and the second block may be a random copolymer or a block copolymer. The repeating unit of the block is not particularly limited.
[0081] The aromatic dicarbonyl compound forming the second block may be, for example, one or more selected from the group consisting of p-Terephthaloyl chloride (TPC), terephthalic acid, isophthaloyl dichloride, and 4,4'-benzoyl chloride. Preferably, the aromatic dicarbonyl compound may be one or more selected from p-Terephthaloyl chloride (TPC) and isophthaloyl dichloride.
[0082] Examples of diamines forming the second block include 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane (HFBAPP), bis(4-(4-aminophenoxy)phenyl)sulfone (BAPS), bis(4-(3-aminophenoxy)phenyl)sulfone (BAPSM), 4,4'-diaminodiphenylsulfone (4DDS), 3,3'-diaminodiphenylsulfone (3DDS), 2,2-bis(4-(4-aminophenoxy)phenylpropane (BAPP), 4,4'-diaminodiphenylpropane (6HDA), 1,3-bis(4-aminophenoxy)benzene (134APB), 1, Examples of the diamine having one or more flexible groups include 3-bis(3-aminophenoxy)benzene (133APB), 1,4-bis(4-aminophenoxy)biphenyl (BAPB), 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FAPBP), 3,3-diamino-4,4-dihydroxydiphenylsulfone (DABS), 2,2-bis(3-amino-4-hydroxyloxyphenyl)propane (BAP), 4,4'-diaminodiphenylmethane (DDM), 4,4'-oxydianiline (4-ODA) and 3,3'-oxydianiline (3-ODA).
[0083] When an aromatic dicarbonyl compound is used, it is easy to realize high thermal stability and mechanical properties, but it may show high birefringence due to the benzene ring in the molecular structure. Therefore, in order to suppress the decrease in birefringence due to the second block, it is preferable to use a diamine having a flexible group introduced into the molecular structure. Specifically, it is more preferable that the diamine is one or more diamines selected from bis(4-(3-aminophenoxy)phenyl)sulfone (BAPSM), 4,4'-diaminodiphenylsulfone (4DDS) and 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane (HFBAPP). In particular, the longer the flexible group is, such as BAPSM, and the more the position of the substituent is in the meta position, the more excellent the birefringence can be shown.
[0084] A polyamideimide precursor having in its molecular structure a first block in which a dianhydride containing biphenyltetracarboxylic dianhydride (BPDA) and 2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA) is copolymerized with a diamine containing bistrifluoromethylbenzidine (TFDB), and a second block in which an aromatic dicarbonyl compound and an aromatic diamine are copolymerized, preferably has a weight average molecular weight measured by GPC of, for example, 200,000 or more and 215,000 or less, and a viscosity of, for example, 2400 poise or more and 2600 poise or less.
[0085] Polyamideimide can be obtained by imidizing a polyamideimide precursor. In addition, a polyamideimide film can be obtained using polyamideimide. For a method for imidizing a polyamideimide precursor and a method for producing a polyamideimide film, for example, JP-T-2018-506611 can be referred to.
[0086] (ii) Aramid resin The aramid resin is not particularly limited as long as it satisfies the above-mentioned composite elastic modulus.
[0087] (iii) Additives The resin layer may further contain additives as necessary, such as ultraviolet absorbers, light stabilizers, antioxidants, inorganic particles, silica fillers for facilitating winding, surfactants for improving film-forming properties and defoaming properties, and adhesion improvers.
[0088] When the resin layer contains an ultraviolet absorbing agent, the deterioration of the resin layer due to ultraviolet rays can be suppressed. In particular, when the resin layer contains polyimide, the color change over time of the resin layer containing polyimide can be suppressed. In addition, in a display device including the laminate, the deterioration of a member arranged on the display panel side of the laminate, such as a polarizer, due to ultraviolet rays can be suppressed.
[0089] Examples of the ultraviolet absorbing agent contained in the resin layer include triazine-based ultraviolet absorbing agents, benzophenone-based ultraviolet absorbing agents such as hydroxybenzophenone-based ultraviolet absorbing agents, and benzotriazole-based ultraviolet absorbing agents.
[0090] Specific examples of triazine-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers such as hydroxybenzophenone-based ultraviolet absorbers, and benzotriazole-based ultraviolet absorbers include those described in JP-A-2019-132930.
[0091] As the ultraviolet absorbing agent, among others, a triazine-based ultraviolet absorbing agent, a hydroxybenzophenone-based ultraviolet absorbing agent, and a benzotriazole-based ultraviolet absorbing agent are preferably used.
[0092] In addition, the ultraviolet absorber is preferably a polymer or oligomer. This is because it is possible to suppress bleeding out of the ultraviolet absorber when the laminate is repeatedly bent. Examples of such ultraviolet absorbers include polymers or oligomers having a triazine skeleton, a benzophenone skeleton, or a benzotriazole skeleton, and specifically, it is preferable that the ultraviolet absorber is a thermal copolymerization of (meth)acrylate having a benzotriazole skeleton or a benzophenone skeleton and methyl methacrylate (MMA) at any ratio.
[0093] The content of the ultraviolet absorbing agent in the resin layer is not particularly limited, but is preferably 1% by mass or more and 6% by mass or less, and more preferably 2% by mass or more and 5% by mass or less. If the content of the ultraviolet absorbing agent is too small, the effect of the ultraviolet absorbing agent may not be sufficiently obtained. If the content of the ultraviolet absorbing agent is too large, the resin layer may be significantly colored or the strength of the resin layer may be reduced.
[0094] (4) Arrangement of deformation suppression layer The method for disposing the deformation suppressing layer may be, for example, a method in which a film-like deformation suppressing layer is bonded to one surface of the glass substrate via a bonding layer.
[0095] When the deformation suppression layer is a resin layer, a method for producing a film-like resin layer can be a general method for producing a resin film, and is appropriately selected depending on the material of the resin layer.
[0096] 2. Bonding layer The bonding layer in the present disclosure is a layer disposed between the glass substrate and the deformation suppression layer for bonding the glass substrate and the deformation suppression layer, and has a thickness smaller than that of the glass substrate.
[0097] The thickness of the bonding layer is thinner than the thickness of the glass substrate, for example, less than 100 μm, preferably 50 μm or less, and more preferably 25 μm or less. If the thickness of the bonding layer is too thick, the bending resistance may be impaired. In addition, since the bonding layer is usually softer than the glass substrate and the deformation suppression layer having a predetermined composite elastic modulus, it is easily deformed by impact, and the thicker the bonding layer, the greater the degree of deformation due to impact tends to be. Therefore, if the thickness of the bonding layer is too thick, when an impact is applied to the laminate, the degree of deformation of the bonding layer increases, and it is considered that instantaneous and local deformation is likely to occur in the glass substrate. In this case, the glass substrate is likely to crack or break, and the impact resistance may be reduced. On the other hand, the thickness of the bonding layer is preferably 0.5 μm or more, more preferably 1 μm or more, and even more preferably 5 μm or more. If the thickness of the bonding layer is too thin, the adhesion may be weakened and peeled off.
[0098] The composite elastic modulus of the bonding layer is, for example, preferably 1.0 MPa or more, more preferably 2.0 MPa or more, and even more preferably 3.0 MPa or more. The composite elastic modulus of the bonding layer is in the above range and has a certain degree of hardness, so that the impact resistance can be improved. In addition, as described above, the bonding layer is usually softer than the glass substrate and the deformation suppression layer having a predetermined composite elastic modulus, so that it is easily deformed by impact, and the smaller the composite elastic modulus of the bonding layer, the greater the degree of deformation due to impact tends to be. Therefore, if the composite elastic modulus of the bonding layer is too small, when an impact is applied to the laminate, the greater the degree of deformation of the bonding layer, so that instantaneous and local deformation is likely to occur in the glass substrate. In this case, the glass substrate is likely to crack or break, and the impact resistance may be reduced. On the other hand, the composite elastic modulus of the bonding layer is, for example, preferably 1.9 GPa or less, more preferably 1.8 GPa or less, and even more preferably 1.5 GPa or less. If the composite elastic modulus of the bonding layer is in the above range, it is softer than the glass substrate and the deformation suppression layer, so that it can absorb impact and improve impact resistance. Moreover, if the composite elastic modulus of the bonding layer is too large, the bending resistance may be impaired.
[0099] The method for measuring the composite elastic modulus of the bonding layer can be the same as the method for measuring the composite elastic modulus of the deformation suppression layer described above.
[0100] The composite elastic modulus of the bonding layer can be adjusted, for example, by the type of material contained in the bonding layer.
[0101] In addition, as described later, when an optically transparent adhesive is used for the bonding layer, the composite elastic modulus of the adhesive can be adjusted by a known method for adjusting the elastic modulus, for example, by adjusting the crosslink density, the type of functional group-containing monomer, etc. For example, the composite elastic modulus tends to increase as the crosslink density increases.
[0102] When the laminate according to the present disclosure is used in, for example, a display device, the bonding layer is preferably transparent. Specifically, the total light transmittance of the bonding layer is preferably 80% or more, more preferably 85% or more, and even more preferably 88% or more.
[0103] The haze of the bonding layer is, for example, preferably 2% or less, more preferably 1.5% or less, and even more preferably 1% or less.
[0104] The material used for the bonding layer is not particularly limited as long as it is a material that can bond the glass substrate and the deformation suppression layer, but it is preferable that the material satisfies the above-mentioned composite elastic modulus and transparency, and examples of the material include an optically clear adhesive (OCA) and a curing adhesive.
[0105] Examples of optically transparent adhesives include acrylic adhesives, urethane adhesives, silicone adhesives, epoxy adhesives, vinyl acetate adhesives, etc. Among these, acrylic adhesives are preferred from the viewpoints of flex resistance, adhesion, and transparency.
[0106] In particular, it is preferable that the optically transparent adhesive satisfies the above-mentioned composite elastic modulus. Commercially available products can be used as such optically transparent adhesives. Specific examples include "8146-2" manufactured by 3M, "MO-3018C", "F619", and "N632" manufactured by Lintec Corporation.
[0107] Examples of the curable adhesive include a thermosetting adhesive and an ultraviolet curable adhesive.
[0108] A thermosetting adhesive is an adhesive that hardens when heated, and examples of the thermosetting adhesive include epoxy adhesives, acrylic adhesives, urethane adhesives, and polyester adhesives.
[0109] The ultraviolet-curing adhesive is an adhesive that is cured by irradiation with ultraviolet light. Examples of the ultraviolet-curing adhesive include an epoxy adhesive and an acrylic adhesive.
[0110] The curable adhesive composition may contain additives as necessary. Examples of additives include light stabilizers, ultraviolet absorbers, infrared absorbers, antioxidants, plasticizers, coupling agents, defoamers, and fillers. These additives can be appropriately selected from commonly used additives. The content of the additives can be appropriately set.
[0111] 3. Glass substrate The thickness of the glass substrate in the present disclosure is 100 μm or less, preferably 90 μm or less, more preferably 80 μm or less. The thickness of the glass substrate is, for example, preferably 15 μm or more, more preferably 20 μm or more, and even more preferably 25 μm or more. By making the thickness of the glass substrate thin in the above range, good flexibility can be obtained and sufficient hardness can be obtained. In addition, curling of the laminate can be suppressed. Furthermore, it is preferable in terms of reducing the weight of the laminate.
[0112] The glass constituting the glass substrate is not particularly limited, but is preferably chemically strengthened glass. Chemically strengthened glass is preferable because it has excellent mechanical strength and can be made thinner accordingly. Chemically strengthened glass is typically glass whose mechanical properties are strengthened by a chemical method by partially exchanging ion species, such as replacing sodium with potassium, near the surface of the glass, and has a compressive stress layer on the surface.
[0113] Examples of the glass constituting the chemically strengthened glass substrate include aluminosilicate glass, soda-lime glass, borosilicate glass, lead glass, alkali barium glass, aluminoborosilicate glass, etc. The chemically strengthened glass substrate may be composed of crystallized glass.
[0114] Commercially available chemically strengthened glass substrates include, for example, Corning's Gorilla Glass, AGC's Dragontrail, and Schott's chemically strengthened glass.
[0115] 4. Functional Layer The laminate of the present disclosure may further include a functional layer on the side of the glass substrate opposite to the bonding layer. Examples of the functional layer include a shatterproof layer, a hard coat layer, an anti-reflection layer, an anti-glare layer, and a protective layer.
[0116] The functional layer may be a single layer or may have multiple layers. The functional layer may be a layer having a single function or may have multiple layers having different functions.
[0117] (1) Anti-scattering layer The laminate in the present disclosure may further include a shatterproof layer 5 on the surface of the glass substrate 2 opposite to the bonding layer 3, as shown in Fig. 2 for example. The shatterproof layer is a layer for preventing glass from shattering. By providing the shatterproof layer, it is possible to prevent glass from shattering even if the glass substrate is broken.
[0118] The composite elastic modulus of the shatterproof layer is, for example, preferably 3 GPa or more, more preferably 3.5 GPa or more, and even more preferably 4.0 GPa or more. The composite elastic modulus of the shatterproof layer within the above range can improve shatterproofness. On the other hand, the composite elastic modulus of the shatterproof layer is, for example, preferably 20 GPa or less, more preferably 17 GPa or less, and even more preferably 15 GPa or less. If the composite elastic modulus of the shatterproof layer is too large, bending resistance may be impaired.
[0119] The method for measuring the composite elastic modulus of the shatterproof layer can be the same as the method for measuring the composite elastic modulus of the deformation suppression layer described above.
[0120] The composite elastic modulus of the shatterproof layer can be adjusted, for example, by the type of material contained in the shatterproof layer.
[0121] The material contained in the shatterproof layer is not particularly limited as long as it can impart shatterproof properties, and various resins can be used, including thermoplastic resins and cured resins cured by exposure to heat or ionizing radiation such as ultraviolet rays or electron beams. Examples of cured resins include thermosetting resins and ionizing radiation cured resins.
[0122] Here, ionizing radiation refers to electromagnetic waves or charged particle beams that have an energy quantum capable of polymerizing or crosslinking molecules. Examples of ionizing radiation include ultraviolet rays and electron beams, as well as electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion beams.
[0123] Among them, the material contained in the shatterproof layer is preferably one that satisfies the above-mentioned composite elastic modulus, and specifically, polyamide, polyimide, polyamideimide, etc. are preferred.
[0124] The shatterproof layer may contain various additives as necessary, such as a filler and a polymerization initiator.
[0125] The thickness of the shatterproof layer is not particularly limited as long as it can exhibit shatterproof function, and is preferably 5 μm or more and 100 μm or less, more preferably 6 μm or more and 95 μm or less, and even more preferably 7 μm or more and 90 μm or less. If the shatterproof layer is too thin, it may be difficult to provide sufficient shatterproof function. Also, if the shatterproof layer is too thick, bending resistance may be impaired.
[0126] The method for forming the shatterproof layer includes, for example, applying a resin composition for shatterproof layer to the surface of the glass substrate opposite to the bonding layer, and curing the resin composition as necessary. By directly forming the shatterproof layer on the surface of the glass substrate opposite to the bonding layer, it is possible to prevent the surface hardness of the laminate on the shatterproof layer side from decreasing.
[0127] (2) Hard coat layer The laminate in the present disclosure may have a hard coat layer on the side opposite to the bonding layer of the glass substrate. In addition, when the laminate has the above-mentioned shatterproof layer, it may further have a hard coat layer 6 on the side opposite to the glass substrate 2 of the shatterproof layer 5, for example, as shown in FIG. 2. The hard coat layer is a layer for increasing the surface hardness. By disposing the hard coat layer, scratch resistance can be improved.
[0128] (a) Characteristics of the hard coat layer Here, the "hard coat layer" refers to a member for increasing surface hardness, and specifically refers to a layer having a hard coat layer in the laminate of the present disclosure, which exhibits a hardness of "H" or more when subjected to a pencil hardness test specified in JIS K 5600-5-4 (1999).
[0129] When the laminate in the present disclosure has a hard coat layer on the side of the shatterproof layer opposite the glass substrate, the pencil hardness of the surface of the laminate on the hard coat layer side is preferably H or more, more preferably 2H or more, and even more preferably 3H or more.
[0130] Here, the pencil hardness is measured by a pencil hardness test specified in JIS K5600-5-4 (1999). Specifically, a pencil hardness test specified in JIS K5600-5-4 (1999) is performed on the surface of the hard coat layer side of the laminate using a test pencil specified in JIS-S-6006, and the highest pencil hardness that does not cause scratches is evaluated. The measurement conditions can be an angle of 45°, a load of 1000 g, a speed of 0.5 mm / sec or more and 1 mm / sec or less, and a temperature of 23±2°C. As a pencil hardness tester, for example, a pencil scratch coating hardness tester manufactured by Toyo Seiki Co., Ltd. can be used.
[0131] (b) Structure of the hard coat layer The hard coat layer may be a single layer or may have a multi-layer structure of two or more layers. When the hard coat layer has a multi-layer structure, in order to improve the surface hardness and to obtain a good balance between the flex resistance and the elastic modulus, the hard coat layer may have a layer for satisfying the pencil hardness and a layer for satisfying the dynamic flex test (a layer for satisfying the scratch resistance).
[0132] (c) Material for hard coat layer As the material for the hard coat layer, for example, an organic material, an inorganic material, or an organic-inorganic composite material can be used.
[0133] Among them, the material of the hard coat layer is preferably an organic material. Specifically, the hard coat layer preferably contains a cured product of a resin composition containing a polymerizable compound. The cured product of the resin composition containing a polymerizable compound can be obtained by polymerizing the polymerizable compound by a known method using a polymerization initiator as necessary.
[0134] (i) Polymerizable compound The polymerizable compound has at least one polymerizable functional group in the molecule. As the polymerizable compound, for example, at least one of a radical polymerizable compound and a cationic polymerizable compound can be used.
[0135] The radical polymerizable compound is a compound having a radical polymerizable group. The radical polymerizable group of the radical polymerizable compound is not particularly limited as long as it is a functional group capable of generating a radical polymerization reaction, and includes, for example, a group containing a carbon-carbon unsaturated double bond, and specifically includes a vinyl group, a (meth)acryloyl group, and the like. In addition, when the radical polymerizable compound has two or more radical polymerizable groups, these radical polymerizable groups may be the same or different from each other.
[0136] The number of radically polymerizable groups that the radically polymerizable compound has in one molecule is preferably 2 or more, and more preferably 3 or more, from the viewpoint of improving the hardness of the hard coat layer.
[0137] As the radical polymerizable compound, from the viewpoint of high reactivity, a compound having a (meth)acryloyl group is preferable. For example, polyfunctional (meth)acrylate monomers and oligomers having several (meth)acryloyl groups in the molecule and a molecular weight of several hundred to several thousand, such as urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, melamine (meth)acrylate, polyfluoroalkyl (meth)acrylate, silicone (meth)acrylate, etc., can be preferably used, and polyfunctional (meth)acrylate polymers having two or more (meth)acryloyl groups in the side chain of an acrylate polymer can also be preferably used. Among them, polyfunctional (meth)acrylate monomers having two or more (meth)acryloyl groups in one molecule can be preferably used. By including a cured product of a polyfunctional (meth)acrylate monomer in the hard coat layer, the hardness of the hard coat layer can be improved, and the adhesion can be further improved. Also preferably used is a polyfunctional (meth)acrylate oligomer or polymer having two or more (meth)acryloyl groups in one molecule. By including a cured product of a polyfunctional (meth)acrylate oligomer or polymer in the hard coat layer, the hardness and flex resistance of the hard coat layer can be improved, and further, the adhesion can be improved.
[0138] In this specification, (meth)acryloyl refers to each of acryloyl and methacryloyl, and (meth)acrylate refers to each of acrylate and methacrylate.
[0139] Specific examples of polyfunctional (meth)acrylate monomers include those described in JP-A-2019-132930. Among these, from the viewpoints of high reactivity, improved hardness of the hard coat layer, and adhesion, those having 3 to 6 (meth)acryloyl groups in one molecule are preferred. For example, pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPPA), trimethylolpropane tri(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, etc. can be preferably used, and in particular, at least one selected from pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexaacrylate, and those modified with PO, EO, or caprolactone are preferred.
[0140] The resin composition may contain a monofunctional (meth)acrylate monomer as a radical polymerizable compound for adjusting hardness and viscosity, improving adhesion, etc. Specific examples of monofunctional (meth)acrylate monomers include those described in JP-A-2019-132930.
[0141] The cationic polymerizable compound is a compound having a cationic polymerizable group. The cationic polymerizable group of the cationic polymerizable compound is not particularly limited as long as it is a functional group capable of generating cationic polymerization reaction, and examples thereof include an epoxy group, an oxetanyl group, and a vinyl ether group. Note that, when the cationic polymerizable compound has two or more cationic polymerizable groups, these cationic polymerizable groups may be the same or different from each other.
[0142] The number of cationically polymerizable groups that the cationically polymerizable compound has in one molecule is preferably 2 or more, and more preferably 3 or more, from the viewpoint of improving the hardness of the hard coat layer.
[0143] In addition, as the cationic polymerizable compound, a compound having at least one of an epoxy group and an oxetanyl group as a cationic polymerizable group is preferable, and a compound having at least two of an epoxy group and an oxetanyl group in one molecule is more preferable. Cyclic ether groups such as an epoxy group and an oxetanyl group are preferable because they cause little shrinkage during polymerization. In addition, compounds having an epoxy group among cyclic ether groups have the advantage that compounds with various structures are easily available, they do not adversely affect the durability of the obtained hard coat layer, and the compatibility with the radical polymerizable compound is easily controlled. In addition, among cyclic ether groups, an oxetanyl group has a higher degree of polymerization and is less toxic than an epoxy group, and when the obtained hard coat layer is combined with a compound having an epoxy group, it has the advantage of accelerating the network formation rate obtained from the cationic polymerizable compound in the coating film, and forming an independent network without leaving unreacted monomers in the film even in the region where it is mixed with the radical polymerizable compound.
[0144] Examples of the cationically polymerizable compound having an epoxy group include alicyclic epoxy resins obtained by epoxidizing a polyglycidyl ether of a polyhydric alcohol having an alicyclic ring or a compound containing a cyclohexene ring or a cyclopentene ring with a suitable oxidizing agent such as hydrogen peroxide or a peracid; aliphatic epoxy resins such as polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts, polyglycidyl esters of aliphatic long-chain polybasic acids, and homopolymers and copolymers of glycidyl (meth)acrylate; glycidyl ethers produced by reacting bisphenols such as bisphenol A, bisphenol F, and hydrogenated bisphenol A, or derivatives thereof such as alkylene oxide adducts or caprolactone adducts, with epichlorohydrin, and novolak epoxy resins, and the like, which are derived from bisphenols.
[0145] Specific examples of the alicyclic epoxy resin, the glycidyl ether type epoxy resin, and the cationic polymerizable compound having an oxetanyl group include those described in JP 2018-104682 A.
[0146] The cured product of the resin composition containing the polymerizable compound contained in the hard coat layer can be analyzed using a Fourier transform infrared spectrophotometer (FTIR) or a pyrolysis gas chromatograph (GC-MS), and the decomposition products of the polymer can be analyzed using a combination of high performance liquid chromatography, a gas chromatograph mass spectrometer, NMR, elemental analysis, XPS / ESCA, TOF-SIMS, etc.
[0147] (ii) Polymerization initiator The resin composition may contain a polymerization initiator as necessary. As the polymerization initiator, a radical polymerization initiator, a cationic polymerization initiator, a radical and cationic polymerization initiator, etc. may be appropriately selected and used. These polymerization initiators are decomposed by at least one of light irradiation and heating to generate radicals or cations, and cause radical polymerization and cationic polymerization to proceed. In addition, there are cases where the polymerization initiator is completely decomposed and does not remain in the hard coat layer.
[0148] Specific examples of radical polymerization initiators and cationic polymerization initiators include those described in JP-A-2018-104682.
[0149] (iii) particles The hard coat layer preferably contains inorganic or organic particles, and more preferably contains inorganic fine particles. When the hard coat layer contains particles, the hardness can be improved.
[0150] Examples of inorganic particles include silica (SiO 2 ), aluminum oxide, zirconia, titania, zinc oxide, germanium oxide, indium oxide, tin oxide, indium tin oxide (ITO), antimony oxide, cerium oxide, and other metal oxide particles, metal fluoride particles, such as magnesium fluoride and sodium fluoride, metal particles, metal sulfide particles, and metal nitride particles. Among these, metal oxide particles are preferred, and at least one selected from silica particles and aluminum oxide particles is more preferred, with silica particles being even more preferred. This is because excellent hardness can be obtained.
[0151] In addition, the inorganic particles are preferably reactive inorganic particles having photoreactive reactive functional groups on at least a part of the particle surface that can form covalent bonds by crosslinking between the inorganic particles themselves or between at least one polymerizable compound. The hardness of the hard coat layer can be further improved by crosslinking between the reactive inorganic particles themselves or between the reactive inorganic particles and at least one of the radical polymerizable compound and the cationic polymerizable compound.
[0152] The reactive inorganic particles have at least a part of the surface covered with an organic component, and have reactive functional groups introduced by the organic component on the surface. For example, a polymerizable unsaturated group is preferably used as the reactive functional group, and more preferably a photocurable unsaturated group. For example, the reactive functional group includes ethylenically unsaturated bonds such as (meth)acryloyl group, vinyl group, and allyl group, and epoxy group.
[0153] The reactive silica particles are not particularly limited, and conventionally known ones can be used, for example, reactive silica particles described in JP-A-2008-165040, etc. In addition, commercially available reactive silica particles include, for example, MIBK-SD, MIBK-SDMS, MIBK-SDL, MIBK-SDZL manufactured by Nissan Chemical Industries, Ltd., and V8802, V8803, etc. manufactured by JGC Catalysts and Chemicals Co., Ltd.
[0154] In addition, silica particles may be spherical silica particles, but preferably are irregular silica particles. Spherical silica particles and irregular silica particles may be mixed. In this specification, irregular silica particles refer to silica particles with random potato-shaped irregularities on the surface. Since irregular silica particles have a larger surface area than spherical silica particles, by including such irregular silica particles, the contact area with the resin component etc. is larger, and the hardness of the hard coat layer can be improved.
[0155] Whether or not the particles are amorphous silica particles can be confirmed by observing a cross section of the hard coat layer with an electron microscope.
[0156] The average particle size of the inorganic particles is preferably 5 nm or more, more preferably 10 nm or more, from the viewpoint of improving hardness. If the average particle size of the inorganic particles is too small, it is difficult to manufacture the particles, and the particles may easily aggregate with each other. In addition, the average particle size of the inorganic particles is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less, from the viewpoint of transparency. If the average particle size of the inorganic particles is too large, there is a risk that large irregularities are formed in the hard coat layer or that the haze is high.
[0157] Here, the average particle size of the inorganic particles can be measured by observing the cross section of the hard coat layer with an electron microscope, and the average particle size is the average of the particle sizes of 10 arbitrarily selected particles. The average particle size of the irregular silica particles is the average value of the maximum (long axis) and minimum (short axis) of the distance between two points on the periphery of the irregular silica particles that appear in the cross section of the hard coat layer observed with a microscope.
[0158] The hardness of the hard coat layer can be controlled by adjusting the size and content of the inorganic particles. For example, the content of the silica particles is preferably 25 parts by mass or more and 120 parts by mass or less with respect to 100 parts by mass of the polymerizable compound.
[0159] (iv) Ultraviolet absorber The hard coat layer may contain an ultraviolet absorbing agent. The deterioration of the deformation suppression layer due to ultraviolet rays can be suppressed. In particular, when the deformation suppression layer contains polyimide, the color change over time of the deformation suppression layer containing polyimide can be suppressed. In addition, in a display device including the laminate, the deterioration of a component arranged on the display panel side of the laminate, such as a polarizer, due to ultraviolet rays can be suppressed.
[0160] The ultraviolet absorber contained in the hard coat layer preferably has an absorption wavelength peak of 300nm or more and 390nm or less in absorbance measurement, more preferably 320nm or more and 370nm or less, and even more preferably 330nm or more and 370nm or less.This is because such an ultraviolet absorber can efficiently absorb ultraviolet rays in the UVA region, and can form a hard coat layer having ultraviolet absorbing ability without causing the hard coat layer to be cured by shifting the peak wavelength from the absorption wavelength of 250nm of the initiator for hardening the hard coat layer.
[0161] Among them, the ultraviolet absorbent preferably has an absorption wavelength peak of 380 nm or less, since coloring due to the ultraviolet absorbent can be suppressed.
[0162] The absorbance of the ultraviolet absorbent can be measured, for example, by using an ultraviolet-visible-near infrared spectrophotometer (for example, V-7100 manufactured by JASCO Corporation).
[0163] The ultraviolet absorbing agent may be the same as the ultraviolet absorbing agent used in the deformation suppressing layer.
[0164] Among these, from the viewpoint of suppressing deterioration of the deformation suppression layer due to ultraviolet rays, one or more ultraviolet absorbers selected from the group consisting of hydroxybenzophenone-based ultraviolet absorbers and benzotriazole-based ultraviolet absorbers are preferred, and one or more ultraviolet absorbers selected from the group consisting of hydroxybenzophenone-based ultraviolet absorbers are more preferred.
[0165] Specific examples of hydroxybenzophenone-based ultraviolet absorbers include those described in JP-A-2019-132930.
[0166] Among them, the hydroxybenzophenone-based ultraviolet absorber is preferably a 2-hydroxybenzophenone-based ultraviolet absorber, and more preferably one or more selected from the group consisting of benzophenone-based ultraviolet absorbers having the following general formula (A). This can suppress deterioration of the deformation-inhibiting layer due to ultraviolet rays and improve durability.
[0167] [ka]
[0168] (In the general formula (A), X 1 and X 2 are each independently a hydroxyl group, -OR a or a hydrocarbon group having 1 to 15 carbon atoms, R a represents a hydrocarbon group having 1 to 15 carbon atoms.
[0169] In the general formula (A), X 1 , X 2 and R a In the above formula, examples of the hydrocarbon group having 1 to 15 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a dodecyl group, an allyl group, and a benzyl group. The aliphatic hydrocarbon groups having 3 or more carbon atoms may each be linear or branched. The hydrocarbon group preferably has 1 to 12 carbon atoms, and more preferably has 1 to 8 carbon atoms. In terms of facilitating an improvement in transparency, the hydrocarbon group is preferably an aliphatic hydrocarbon group, and among these, a methyl group and an allyl group are preferred.
[0170] X is a material that is easy to improve durability. 1 and X 2 each independently represents a hydroxyl group or -OR a It is preferable that:
[0171] The one or more types selected from the group consisting of benzophenone-based ultraviolet absorbers having general formula (A) are preferably one or more types selected from the group consisting of 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and 2,2'-dihydroxy-4,4'-diallyloxybenzophenone, and more preferably one or more types selected from the group consisting of 2,2',4,4'-tetrahydroxybenzophenone and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone.
[0172] Specific examples of benzotriazole-based ultraviolet absorbers include those described in JP-A-2019-132930.
[0173] Among them, the benzotriazole-based ultraviolet absorber is preferably 2-(2-hydroxyphenyl)benzotriazoles, and more preferably one or more selected from the group consisting of benzotriazole-based ultraviolet absorbers having the following general formula (B): Deterioration of the deformation suppression layer caused by ultraviolet rays can be suppressed, and durability can be improved.
[0174] [ka]
[0175] (In the general formula (B), Y 1 , Y 2 , and Y 3 are each independently a hydrogen atom, a hydroxyl group, -OR b or a hydrocarbon group having 1 to 15 carbon atoms, R b represents a hydrocarbon group having 1 to 15 carbon atoms; Y 1 , Y 2 , and Y 3 At least one of the groups is a hydroxyl group, -OR b or a hydrocarbon group having 1 to 15 carbon atoms. 4 represents a hydrogen atom or a halogen atom.
[0176] In the general formula (B), Y 1 , Y 2 , and Y 3 , and R b In the above formula, examples of the hydrocarbon group having 1 to 15 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, and a dodecyl group. The aliphatic hydrocarbon group having 3 or more carbon atoms may be linear or branched. The hydrocarbon group preferably has 1 to 12 carbon atoms, and more preferably has 1 to 8 carbon atoms. In terms of easiness in improving transparency, the hydrocarbon group is preferably an aliphatic hydrocarbon group, and is preferably a linear or branched alkyl group, and among these, a methyl group, a t-butyl group, a t-pentyl group, a n-octyl group, or a t-octyl group is preferable.
[0177] In the general formula (B), Y 4 Examples of the halogen atom in include a chlorine atom, a fluorine atom, and a bromine atom, and among these, a chlorine atom is preferred.
[0178] In the general formula (B), Y 1 , and Y 3 is a hydrogen atom, and Y 2 is a hydroxyl group or -OR b It is preferable that the compound is one or more selected from the group consisting of 2-(2-hydroxy-4-octyloxyphenyl)-2H-benzotriazole and 2-(2,4-dihydroxyphenyl)-2H-benzotriazole. It is possible to suppress deterioration of the deformation suppressing layer caused by ultraviolet rays and improve durability.
[0179] The content of the ultraviolet absorber in the hard coat layer is, for example, preferably 10% by mass or less, more preferably 7% by mass or less, from the viewpoint of suppressing haze caused by mixing the ultraviolet absorber. Also, from the viewpoint of suppressing deterioration of the deformation suppression layer due to ultraviolet rays and improving durability, the content of the ultraviolet absorber in the hard coat layer is preferably 1% by mass or more and 6% by mass or less, more preferably 2% by mass or more and 5% by mass or less.
[0180] (v) Antifouling agents The hard coat layer may contain an antifouling agent, which can impart antifouling properties to the laminate.
[0181] The antifouling agent is not particularly limited, and examples thereof include silicone-based antifouling agents, fluorine-based antifouling agents, and silicone-based and fluorine-based antifouling agents. The antifouling agent may also be an acrylic-based antifouling agent. The antifouling agent may be used alone or in combination of two or more.
[0182] The hard coat layer containing the silicone-based antifouling agent or the fluorine-based antifouling agent is less susceptible to fingerprints (less noticeable) and has good wiping properties. In addition, when the silicone-based antifouling agent or the fluorine-based antifouling agent is contained, the surface tension during application of the hard coat layer curable resin composition can be reduced, resulting in good leveling properties and a good appearance of the obtained hard coat layer.
[0183] In addition, the hard coat layer containing the silicone-based antifouling agent has good slipperiness and good scratch resistance. In a display device including a laminate having a hard coat layer containing such a silicone-based antifouling agent, the slipperiness when touched with a finger, a pen, or the like is improved, resulting in a good tactile sensation.
[0184] The antifouling agent preferably has a reactive functional group in order to enhance the durability of the antifouling performance. If the antifouling agent does not have a reactive functional group, regardless of whether the laminate is in the form of a roll or a sheet, when the laminate is stacked, the antifouling agent is transferred to the surface opposite to the hard coat layer side of the laminate, and when another layer is attached or applied to the surface opposite to the hard coat layer side of the laminate, the other layer may peel off, and further, when repeatedly bent, the other layer may easily peel off. On the other hand, when the antifouling agent has a reactive functional group, the performance durability of the antifouling performance is good.
[0185] The number of reactive functional groups in the antifouling agent may be at least 1, and is preferably at least 2. By using an antifouling agent having two or more reactive functional groups, excellent scratch resistance can be imparted to the hard coat layer.
[0186] The antifouling agent preferably has a weight average molecular weight of not more than 5000. The weight average molecular weight of the antifouling agent can be measured by gel permeation chromatography (GPC).
[0187] The antifouling agent may be uniformly dispersed in the hard coat layer. However, from the viewpoint of obtaining sufficient antifouling properties with a small amount of addition and suppressing a decrease in strength of the hard coat layer, it is preferable that the antifouling agent is unevenly distributed on the surface side of the hard coat layer.
[0188] Examples of the method for unevenly distributing the antifouling agent on the surface side of the hard coat layer include a method in which, when forming the hard coat layer, a coating film of a curable resin composition for a hard coat layer is dried and before being cured, the coating film is heated to reduce the viscosity of the resin component contained in the coating film, thereby increasing the fluidity, thereby unevenly distributing the antifouling agent on the surface side of the hard coat layer; and a method in which an antifouling agent with low surface tension is used, the antifouling agent is floated on the surface of the coating film without applying heat when the coating film is dried, and then the coating film is cured, thereby unevenly distributing the antifouling agent on the surface side of the hard coat layer.
[0189] The content of the antifouling agent is preferably, for example, 0.01 parts by mass or more and 3.0 parts by mass or less relative to 100 parts by mass of the resin component. If the content of the antifouling agent is too small, sufficient antifouling properties may not be imparted to the hard coat layer, and if the content of the antifouling agent is too large, the hardness of the hard coat layer may decrease.
[0190] (vi) Other additives The hard coat layer may further contain additives as necessary.The additives are appropriately selected according to the function to be imparted to the hard coat layer, and are not particularly limited, and may include, for example, inorganic or organic particles for adjusting the refractive index, infrared absorbing agents, antiglare agents, antifouling agents, antistatic agents, colorants such as blue dyes and purple dyes, leveling agents, surfactants, lubricants, various sensitizers, flame retardants, adhesion promoters, polymerization inhibitors, antioxidants, light stabilizers, surface modifiers, etc.
[0191] (d) Thickness of the hard coat layer The thickness of the hard coat layer may be appropriately selected depending on the material of the hard coat layer, the function of the hard coat layer, and the use of the laminate. For example, when the material of the hard coat layer is an organic material, the thickness of the hard coat layer is preferably 2 μm or more and 50 μm or less, more preferably 3 μm or more and 30 μm or less, even more preferably 5 μm or more and 20 μm or less, and particularly preferably 6 μm or more and 10 μm or less. In addition, for example, when the material of the hard coat layer is an inorganic material, the thickness of the hard coat layer can be about several tens of nm. If the thickness of the hard coat layer is within the above range, a laminate having sufficient hardness as a hard coat layer and good bending resistance can be obtained.
[0192] (e) Method for forming hard coat layer The method for forming the hard coat layer is appropriately selected depending on the material of the hard coat layer, and examples thereof include a method of applying a hard coat layer curable resin composition containing the above-mentioned polymerizable compound to the surface of the glass substrate opposite to the bonding layer, and curing the composition, a vapor deposition method, a sputtering method, etc. By directly forming a hard coat layer on the surface of the glass substrate opposite to the bonding layer, it is possible to suppress a decrease in the surface hardness of the laminate on the hard coat layer side.
[0193] The curable resin composition for a hard coat layer contains a polymerizable compound, and may further contain a polymerization initiator, particles, an ultraviolet absorber, a solvent, additives, and the like, as necessary.
[0194] The method for applying the curable resin composition for hard coat layer onto the shatterproof layer is not particularly limited as long as it is a method that allows application to a desired thickness, and examples of the method include general application methods such as gravure coating, gravure reverse coating, gravure offset coating, spin coating, roll coating, reverse roll coating, blade coating, dip coating, spray coating, die coating, screen printing, etc. In addition, a transfer method can also be used as a method for forming a coating film of the resin composition for hard coat layer.
[0195] The coating film of the curable resin composition for hard coat layer is dried as necessary to remove the solvent. Examples of the drying method include vacuum drying, heat drying, and a combination of these drying methods. For example, the coating film can be dried by heating at a temperature of 30° C. or higher and 120° C. or lower for 10 seconds to 180 seconds.
[0196] The method for curing the coating of the curable resin composition for the hard coat layer is appropriately selected depending on the polymerizable group of the polymerizable compound, and for example, at least one of light irradiation and heating can be used.
[0197] For light irradiation, ultraviolet light, visible light, electron beams, ionizing radiation, etc. are mainly used. In the case of ultraviolet curing, for example, ultraviolet light emitted from the light beam of an ultra-high pressure mercury lamp, a high pressure mercury lamp, a low pressure mercury lamp, a carbon arc, a xenon arc, a metal halide lamp, etc. can be used. The irradiation amount of the energy ray source is, for example, 50 mJ / cm as the cumulative exposure amount at an ultraviolet wavelength of 365 nm. 2 More than 5000mJ / cm 2 It can be as follows:
[0198] When heating is performed, the treatment can be performed at a temperature of, for example, 40° C. or higher and 120° C. or lower. The reaction may also be performed by leaving the mixture at room temperature (25° C.) for 24 hours or more.
[0199] 5. Properties of Laminates When the laminate in the present disclosure is used in a display device, it is preferable that the laminate has transparency. Specifically, the total light transmittance of the laminate in the present disclosure is, for example, preferably 80% or more, more preferably 85% or more, and even more preferably 88% or more. By having such a high total light transmittance, the laminate can have good transparency.
[0200] The total light transmittance of the laminate can be measured in accordance with JIS K7361-1, for example, by using a haze meter HM150 manufactured by Murakami Color Research Laboratory.
[0201] The haze of the laminate in the present disclosure is, for example, preferably 2% or less, more preferably 1.5% or less, and even more preferably 1% or less. Such a low haze allows the laminate to have good transparency.
[0202] The haze of the laminate can be measured in accordance with JIS K-7136, for example, by using a haze meter HM150 manufactured by Murakami Color Research Laboratory.
[0203] The laminate in the present disclosure preferably has flex resistance. Specifically, it is preferable that the laminate in the present disclosure does not crack or break when subjected to a dynamic flex test described below.
[0204] In the dynamic bending test, the laminate may be folded so that the glass substrate is on the outside, or the laminate may be folded so that the glass substrate is on the inside, but in either case, it is preferable that the laminate does not crack or break.
[0205] The dynamic bending test is carried out as follows. As shown in FIG. 3(a), in the dynamic bending test, first, the short side 1C of the laminate 1 having a size of 20 mm×100 mm and the short side 1D opposite to the short side 1C are fixed by the fixing parts 21 arranged in parallel. Also, as shown in FIG. 3(a), the fixing parts 21 are slidable in the horizontal direction. Next, as shown in FIG. 3(b), the fixing parts 21 are moved so as to approach each other, so that the laminate 1 is deformed so as to be folded, and further, as shown in FIG. 3(c), the fixing parts 21 are moved to a position where the distance d between the two opposing short side parts 1C and 1D fixed by the fixing parts 21 of the laminate 1 becomes a predetermined value, and then the fixing parts 21 are moved in the opposite direction to eliminate the deformation of the laminate 1. As shown in FIG. 3(a) to (c), the fixing parts 21 can be moved to fold the laminate 1 by 180°. Furthermore, by performing a dynamic bending test so that the bent portion 1E of the laminate 1 does not protrude from the lower end of the fixed portion 21 and controlling the distance d when the fixed portion 21 is closest, the distance d between the two opposing short side portions 1C, 1D of the laminate 1 can be set to a predetermined value. For example, when the distance d between the two opposing short side portions 1C, 1D is 10 mm, the outer diameter of the bent portion 1E is regarded as 10 mm.
[0206] It is preferable that the laminate does not crack or break when a test in which the laminate is folded 180° so that the distance d between the opposing short side portions 1C, 1D of the laminate 1 is 10 mm is repeated 100,000 times, and it is even more preferable that no crack or break occurs when the test is repeated 200,000 times.
[0207] Furthermore, in the laminate of the present disclosure, when the laminate is subjected to a static bending test described below, the opening angle θ of the laminate after the static bending test is preferably 100° or more, and more preferably 130° or more.
[0208] The static bending test is carried out as follows. First, as shown in FIG. 4(a), the short side 1C of the laminate 1 having a size of 20 mm×100 mm and the short side 1D facing the short side 1C are fixed by the fixing parts 22 arranged in parallel so that the distance d between the short side 1C and the short side 1D is 10 mm. Then, the laminate 1 is folded and left to stand at 23° C. for 240 hours to carry out a static bending test. After that, as shown in FIG. 4(b), the fixing parts 22 are removed from the short side 1D after the static bending test to open the folded state, and the opening angle θ, which is the angle at which the laminate 1 naturally opens after 30 minutes at room temperature, is measured. The larger the opening angle θ, the better the restorability, and the maximum opening angle is 180°.
[0209] In the static bending test, the laminate may be folded so that the glass substrate is on the inside, or the laminate may be folded so that the glass substrate is on the outside. In either case, the opening angle θ is preferably 100° or more, and more preferably 130° or more.
[0210] 6. Applications of laminates The use of the laminate in the present disclosure is not particularly limited, and for example, the laminate can be used as a member arranged on the viewer side of a display panel in a display device. The laminate in the present disclosure can be used in display devices such as smartphones, tablet terminals, wearable terminals, personal computers, televisions, digital signage, public information displays (PIDs), and in-vehicle displays.
[0211] The laminate in the present disclosure has good bending resistance and impact resistance, and therefore can be preferably used as a member that can accommodate curved surfaces. The laminate in the present disclosure can be preferably used for flexible displays such as foldable displays, rollable displays, and bendable displays, and is more preferably used for foldable displays. In addition, the laminate in the present disclosure can be used as a surface material for resin molded products having curved surfaces, and can provide design and aesthetics.
[0212] When the laminate according to the present disclosure is disposed on the surface of a display device, a resin molded product, or the like, it is disposed so that the surface on the deformation suppression layer side is on the inner side and the surface on the glass substrate side is on the outer side.
[0213] The method for disposing the laminate of the present disclosure on the surface of a display device, a resin molded product, etc. is not particularly limited, and examples thereof include a method using an adhesive layer, etc. As the adhesive layer, a known adhesive layer used for bonding laminates can be used.
[0214] B.Display device The display device of the present disclosure comprises a display panel and the above-mentioned laminate arranged on the observer side of the display panel, and the laminate is arranged so that the surface on the deformation suppression layer side faces the display panel.
[0215] Fig. 5 is a schematic cross-sectional view showing an example of a display device according to the present disclosure. As shown in Fig. 5, a display device 30 includes a display panel 31 and a laminate 1 arranged on the viewer's side of the display panel 31. The laminate 1 is arranged so that the surface on the deformation suppression layer 4 side faces the display panel 31. In the display device 30, the laminate 1 is used as a member arranged on the surface of the display device 30, and an adhesive layer 32 is arranged between the laminate 1 and the display panel 31.
[0216] The laminate in the present disclosure may be similar to the laminate described above.
[0217] Examples of the display panel in the present disclosure include display panels used in display devices such as liquid crystal display devices, organic EL display devices, and LED display devices.
[0218] The display device according to the present disclosure may have a touch panel member between the display panel and the laminate.
[0219] The display device in the present disclosure is preferably a flexible display. In particular, the display device in the present disclosure is preferably foldable. That is, the display device in the present disclosure is more preferably a foldable display. Since the display device in the present disclosure has the above-mentioned laminate, it has excellent impact resistance and bending resistance, and is suitable as a flexible display and even a foldable display.
[0220] In the laminate of the present disclosure, the distance from the surface of the laminate on the deformation suppression layer side to the surface of the display panel on the viewer side is preferably, for example, 150 μm or less. By having the distance in the above range, it is possible to improve impact resistance.
[0221] Here, the distance from the surface of the laminate on the deformation suppression layer side to the surface of the display panel on the viewer side is, for example, the distance indicated by d in FIG.
[0222] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0223] The present disclosure will be further described below with reference to examples and comparative examples.
[0224] [Comparative Example 1] A chemically strengthened glass substrate with a thickness of 70 μm was used.
[0225] [Comparative Example 2] A chemically strengthened glass substrate with a thickness of 100 μm was used.
[0226] [Comparative Example 3] A chemically strengthened glass substrate having a thickness of 70 μm and a PET film having a thickness of 70 μm ("Cosmoshine A4100" manufactured by Toyobo Co., Ltd.) were bonded together via a bonding layer having a thickness of 25 μm (OCA film, acrylic adhesive film "8146-1" manufactured by 3M Co., Ltd.) to produce a laminate.
[0227] [Example 1] (Creation of deformation suppression layer) With reference to Synthesis Example 1 of WO 2014 / 046180, a tetracarboxylic dianhydride represented by the following chemical formula was synthesized.
[0228] [ka]
[0229] A solution of dehydrated N,N-dimethylacetamide (DMAc) (1833.2 g) and 2,2'-bis(trifluoromethyl)benzidine (TFMB) (138.48 g) was placed in a 5L separable flask, and the liquid temperature was controlled at 30°C. Tetracarboxylic dianhydride (TMPBPTME) (176.70 g) represented by the above chemical formula was gradually added so that the temperature rise was 2°C or less, and the mixture was stirred with a mechanical stirrer for 30 minutes. Pyromellitic dianhydride (PMDA) (64.20 g) was gradually added in several portions so that the temperature rise was 2°C or less, synthesizing a polyimide precursor solution (solid content 18% by mass) in which the polyimide precursor was dissolved. The molar ratio (TMPBPTME:PMDA) of the tetracarboxylic dianhydride TMPBPTME and PMDA used in the polyimide precursor was 90:10. The weight average molecular weight of the polyimide precursor was 75,000.
[0230] Under a nitrogen atmosphere, the above polyimide precursor solution (2162 g) was added to a 5 L separable flask, cooled to room temperature. Dehydrated N,N-dimethylacetamide (432 g) was added and stirred until homogenous. Next, catalysts pyridine (6.622 g) and acetic anhydride (213.67 g) were added and stirred at room temperature for 24 hours to synthesize a polyimide solution.
[0231] N,N-dimethylacetamide (DMAc) (2000 g) was added to the obtained polyimide solution and stirred until it became uniform. Next, the polyimide solution was divided into three equal parts and transferred to a 5 L beaker, and isopropyl alcohol (3500 g) was gradually added to each beaker to obtain a white slurry. The above slurry was transferred onto a Buchner funnel and filtered, and then washed with isopropyl alcohol (total 9000 g), and the process of filtering was repeated three times, and the mixture was dried at 110 ° C using a vacuum dryer to obtain polyimide (polyimide powder). The weight average molecular weight of the polyimide measured by GPC was 100,000.
[0232] A polyimide varnish (resin composition) containing 12% by mass of polyimide was prepared by adding N,N-dimethylacetamide (DMAc) to the polyimide so that the solid content of the polyimide was 12% by mass. The viscosity of the polyimide varnish (resin composition) (solid content concentration 12% by mass) at 25°C was 15000cps.
[0233] A polyimide varnish (solid content concentration: 12% by mass) was applied onto a glass plate so that the film thickness after drying in a circulating oven described below would be the thickness shown in Table 1. The plate was then dried in a circulating oven at 120°C for 10 minutes, cooled to 25°C, and the polyimide resin coating was peeled off.
[0234] The peeled polyimide resin coating film was cut into a size of 150 mm x 200 mm. The cut polyimide resin coating film was sandwiched between two metal frames (outer dimensions 150 mm x 200 mm, inner dimensions 130 mm x 180 mm), and the metal frames and the polyimide resin coating film were fixed with a fixing jig. The fixed polyimide resin coating film was heated to 300°C at a heating rate of 10°C / min in a circulating oven under a nitrogen flow (oxygen concentration 100 ppm or less), held at 300°C for 1 hour, and then cooled to 25°C to produce a single-layer polyimide film.
[0235] (Preparation of Laminate) A chemically strengthened glass substrate having a thickness of 70 μm and the above-mentioned deformation suppression layer (polyimide film) were bonded together via a bonding layer having a thickness of 25 μm (OCA film, acrylic adhesive film "8146-1" manufactured by 3M Corporation) to produce a laminate.
[0236] [Example 2] Two chemically strengthened glass substrates each having a thickness of 70 μm were bonded together via a bonding layer having a thickness of 25 μm (OCA film, acrylic adhesive film "8146-1" manufactured by 3M Corporation) to produce a laminate.
[0237] [Example 3] (Formation of shatterproof layer) The polyimide varnish (resin composition) used in Example 1 was applied to a predetermined thickness on a chemically strengthened glass substrate having a thickness of 70 μm, and dried at 100°C for 10 minutes, at 150°C for 10 minutes, and at 230°C for 30 minutes to form a shatterproof layer having a thickness of 20 μm.
[0238] (Formation of hard coat layer) The components were mixed so as to obtain the composition shown below, thereby preparing a curable resin composition for a hard coat layer.
[0239] <Composition of Curable Resin Composition for Hard Coat Layer> Mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.) 25 parts by weight Dipentaerythritol EO modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 25 parts by weight -50 parts by weight (solid equivalent) of non-standard silica particles (average particle size 25 nm, manufactured by JGC Catalysts and Chemicals) Photopolymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV) 4 parts by weight Fluorine-based leveling agent (F568, DIC Corporation) 0.2 parts by weight (solid equivalent) Ultraviolet absorber 1 (DAINSORB P6, manufactured by Daiwa Kasei) 3 parts by weight Solvent (MIBK) 150 parts by weight
[0240] The curable resin composition for hard coat layer was applied to the shatterproof layer to a predetermined thickness, dried at 80° C. for 3 minutes, and then cured by UV irradiation to form a hard coat layer having a thickness of 10 μm. This resulted in a laminate A in which the glass substrate, the shatterproof layer, and the hard coat layer were arranged in this order.
[0241] (Preparation of Laminate) A 70 μm-thick chemically strengthened glass substrate was used as the deformation suppression layer, and this glass substrate was bonded to the glass substrate side surface of the laminate A via a 25 μm-thick bonding layer (OCA film, acrylic adhesive film "8146-1" manufactured by 3M).
[0242] [Example 4] A laminate was produced in the same manner as in Example 3, except that a chemically strengthened glass substrate having a thickness of 50 μm was used as the deformation suppression layer.
[0243] [Example 5] A laminate was produced in the same manner as in Example 3, except that a chemically strengthened glass substrate having a thickness of 30 μm was used as the deformation suppression layer.
[0244] [Example 6] A laminate was produced in the same manner as in Example 3, except that a chemically strengthened glass substrate having a thickness of 50 μm was used as the glass substrate.
[0245] [Example 7] A laminate was produced in the same manner as in Example 3, except that a chemically strengthened glass substrate having a thickness of 50 μm was used as the glass substrate, and a chemically strengthened glass substrate having a thickness of 50 μm was used as the deformation suppression layer.
[0246] [Example 8] A laminate was produced in the same manner as in Example 3, except that a chemically strengthened glass substrate having a thickness of 50 μm was used as the glass substrate, and a chemically strengthened glass substrate having a thickness of 30 μm was used as the deformation suppression layer.
[0247] [Example 9] A laminate was produced in the same manner as in Example 3, except that a 50 μm-thick bonding layer (OCA film, acrylic adhesive film “8146-2” manufactured by 3M) was used as the bonding layer.
[0248] [Example 10] A laminate was produced in the same manner as in Example 3, except that a 5 μm-thick adhesive layer (OCA film, acrylic adhesive film "Panaclean PD-S1" manufactured by Panac Corporation) was used as the adhesive layer.
[0249] [Comparative Example 4] A laminate was produced in the same manner as in Example 3, except that a 100 μm-thick bonding layer (OCA film, acrylic adhesive film “8146-4” manufactured by 3M) was used as the bonding layer.
[0250] [Example 11] (Formation of shatterproof layer and hard coat layer) In the same manner as in Example 3, a shatterproof layer and a hard coat layer were formed on a glass substrate, to obtain a laminate A in which the glass substrate, the shatterproof layer, and the hard coat layer were arranged in this order.
[0251] (Formation of adhesive layer) The components were mixed so as to obtain the composition shown below, thereby preparing an ultraviolet-curable resin composition.
[0252] <Composition of UV-curable resin composition> Urethane acrylate (product name "UV-3310B", manufactured by Mitsubishi Chemical Corporation): 35 parts by weight Ethoxylated pentaerythritol tetraacrylate (product name "ATM-35E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 10 parts by mass Phenoxyethyl acrylate (product name "Viscoat #192", manufactured by Osaka Organic Chemical Industry Co., Ltd.): 5 parts by weight Mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate (product name "KAYARAD PET-30", manufactured by Nippon Kayaku Co., Ltd.): 50 parts by weight Polymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV): 5 parts by mass Methyl isobutyl ketone: 10 parts by weight
[0253] A chemically strengthened glass substrate having a thickness of 70 μm was used as the deformation suppression layer, and the above-mentioned ultraviolet-curable resin composition was applied to the glass substrate to a predetermined thickness, and heated at 100° C. for 1 minute to form an adhesive layer having a thickness of 25 μm. This resulted in a laminate B having a glass substrate and an adhesive layer.
[0254] (Preparation of Laminate) The glass substrate side surface of the laminate A and the adhesive layer side surface of the laminate B were overlapped, and ultraviolet rays were irradiated from the laminate B side using an ultraviolet irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb) at an integrated light amount of 400 mJ / cm in air. 2 The adhesive layer was cured to form a bonding layer, thereby producing a laminate.
[0255] [Example 12] A laminate was produced in the same manner as in Example 11, except that the thickness of the adhesive layer was 5 μm.
[0256] [Example 13] A laminate was produced in the same manner as in Example 11, except that the thickness of the adhesive layer was 0.5 μm.
[0257] [Example 14] A laminate was produced in the same manner as in Example 12, except that the following ultraviolet-curable resin composition was used in forming the adhesive layer.
[0258] <Composition of UV-curable resin composition> Urethane acrylate (product name "UV-3310B", manufactured by Mitsubishi Chemical Corporation): 15 parts by weight Ethoxylated pentaerythritol tetraacrylate (product name "ATM-35E", manufactured by Shin-Nakamura Chemical Co., Ltd.): 30 parts by mass Dicyclopentanyl acrylate (product name "FA-513AS", manufactured by Hitachi Chemical Co., Ltd.): 5 parts by weight Dipentaerythritol hexaacrylate (product name: "KAYARAD DPHA", manufactured by Nippon Kayaku Co., Ltd.): 50 parts by weight Polymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad184", manufactured by IGM Resins BV): 5 parts by mass Methyl isobutyl ketone: 10 parts by weight
[0259] [Example 15] A laminate was produced in the same manner as in Example 3, except that a 25 μm-thick bonding layer (OCA film, “F619” manufactured by Lintec Corporation) was used as the bonding layer.
[0260] [evaluation] (1) Composite elastic modulus The composite elastic modulus of the deformation suppression layer and the bonding layer was measured by the above-mentioned method for measuring the composite elastic modulus.
[0261] (2) Impact test (pen drop test) Impact tests were performed on the laminates of Examples 1 to 15 and Comparative Examples 3 and 4, and the glass substrates of Comparative Examples 1 and 2. First, a 100 μm thick PET film ("A4100" manufactured by Toyobo Co., Ltd.) was attached to the deformation suppression layer side of the laminates for Examples 1 to 15, and to the glass substrate for Comparative Examples 1 and 2, via a 50 μm thick optical adhesive film (OCA) ("8146-2" manufactured by 3M Co., Ltd.) to prepare a test laminate. The test laminate was placed on a metal plate with the PET film side of the test laminate in contact with the metal plate having a thickness of 30 mm. Next, a pen was dropped on the test laminate from the test height with its tip facing down against the center of the test laminate. Zebra's Blen 0.5BAS88-BK (weight 12 g, pen tip 0.5 mmφ) was used as the pen. Tables 1 to 3 show the maximum test height at which the glass substrate did not crack. The larger the value, the higher the impact resistance.
[0262] (3) Dynamic bending test The laminates of Examples 1 to 15 and Comparative Examples 3 and 4 and the glass substrate of Comparative Examples 1 and 2 were subjected to the dynamic bending test described above to evaluate bending resistance. In this case, the distance d between two opposing short sides of the laminate or the glass substrate was 10 mm. The laminate was bent so that the glass substrate was on the inside and the deformation suppression layer was on the outside. The results of the dynamic bending test were evaluated according to the following criteria. A: No cracks or breaks in the glass substrate or deformation suppression layer even after 200,000 cycles B: No cracks or breaks in the glass substrate or deformation suppression layer even after 100,000 cycles C: Cracks or breaks occurred in the glass substrate and the deformation suppression layer after 100,000 cycles or less.
[0263] (4) Pencil hardness First, a 100 μm thick PET film ("A4100" manufactured by Toyobo Co., Ltd.) was attached to the deformation suppression layer side of the laminate for Examples 1 to 15, and to the glass substrate for Comparative Examples 1 and 2, via a 50 μm thick optical adhesive film (OCA) ("8146-2" manufactured by 3M Co., Ltd.) to prepare a test laminate. For the laminates of Examples 1 to 2 and Comparative Example 3, the pencil hardness was measured on the surface of the glass substrate side of the test laminate. For the laminates of Examples 3 to 15 and Comparative Example 4, the pencil hardness was measured on the surface of the hard coat layer side of the test laminate. For the glass substrates of Comparative Examples 1 to 2, the pencil hardness was measured on the surface of the glass substrate side of the test laminate. At this time, the pencil hardness was measured in accordance with JIS K5600-5-4 (1999). A pencil hardness tester (product name: "Pencil Scratch Coating Hardness Tester (electric type)" manufactured by Toyo Seiki Seisakusho Co., Ltd.) was used, and the measurement conditions were an angle of 45°, a load of 1000 g, a speed of 0.5 mm / sec to 1 mm / sec, and a temperature of 23±2°C. A pencil hardness of 5H or more indicates good scratch resistance.
[0264] [Table 1]
[0265] [Table 2]
[0266] [Table 3]
[0267] It is apparent from Tables 1 to 3 that good impact resistance can be obtained when the composite elastic modulus of the deformation suppression layer is within a predetermined range and the thickness of the bonding layer is thinner than the thickness of the glass substrate. [Explanation of symbols]
[0268] 1 … Laminate 2 … Glass substrate 3 … Bonding layer 4 ... Deformation suppression layer 5 … Anti-scattering layer 6 … Hard coat layer 30…Display device 31 ... Display panel
Claims
1. The glass substrate, the bonding layer, and the deformation suppression layer are provided in this order. The glass constituting the glass substrate is chemically strengthened glass, The thickness of the glass substrate is 15 μm or more and 90 μm or less, The deformation suppression layer has a composite elastic modulus of 7.0 GPa or more, The thickness of the deformation suppression layer is 25 μm or more and 90 μm or less, A laminate, wherein the thickness of the bonding layer is thinner than the thickness of the glass substrate, The laminate does not crack or break when a test in which the laminate is folded 180° so that the distance between two opposing short sides of the laminate is 10 mm is repeated 100,000 times.
2. The laminate according to claim 1 , wherein the bonding layer has a composite elastic modulus of 1.0 MPa or more and 1.9 GPa or less.
3. The laminate according to claim 1 or 2, wherein the deformation suppression layer is a glass layer.
4. 3. The laminate according to claim 1, wherein the deformation suppression layer is a resin layer containing a polyimide resin or an aramid resin.
5. The laminate according to claim 1 , further comprising a shatterproof layer on a surface of the glass substrate opposite to the bonding layer.
6. The laminate according to claim 5 , further comprising a hard coat layer on the surface of the shatterproof layer opposite to the glass substrate.
7. The laminate according to any one of claims 1 to 6, which has a total light transmittance of 80% or more and a haze of 2% or less.
8. A display panel; A laminate according to any one of claims 1 to 7, which is disposed on a viewer side of the display panel; the laminate is disposed so that a surface of the laminate on the deformation suppression layer side faces the display panel.
9. The display device according to claim 8, which is foldable.
Citation Information
Patent Citations
Scattering preventing film for image display device and image display device equipped with the same
JP2011209512A
Manufacturing method of laminate, laminate, and electronic device
JP2013014135A
Layered, flexible, puncture-resistant glass articles and methods of manufacture
JP2020500143A
Flexible, ultra-thin glass with high contact resistance
JP2020521699A
Quasi-static and dynamic shock-resistant display module
JP2020536773A